(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article examines the current problems related to the qualitative characteristics of accounting information. Special attention is given to attributes such as relevance, reliability, timeliness, and transparency, as well as the underlying causes of their insufficient fulfillment. It is substantiated that the misalignment between national accounting standards and International Financial Reporting Standards (IFRS), technological limitations, subjectivity in valuation, and weaknesses in information systems contribute to the decline in the quality of accounting information. As a solution, the paper proposes the integration of quantitative and qualitative approaches, the adoption of modern digital technologies, and alignment with international standards. The study analyzes the works of both national and foreign scientists and presents practical recommendations for addressing the identified issues.